2004
DOI: 10.1161/01.cir.0000112581.96154.ea
|View full text |Cite
|
Sign up to set email alerts
|

Serum Homocysteine in Relation to Mortality and Morbidity From Coronary Heart Disease

Abstract: Background-Elevated serum total homocysteine (tHcy) is an established risk factor for cardiovascular disease (CVD), especially in men. However, there are few prospective population studies on female cohorts, and none of these has been longer than 13 years. Gothenburg began in 1968Gothenburg began in /1969, at which time a representative population-based cohort of women aged 38, 46, 50, 54, and 60 years was recruited. The present cohort is a prospective follow-up of 1368 women in the original cohort for whom b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 34 publications
11
54
1
1
Order By: Relevance
“…Taken together, these findings do not support a strong role for either homocysteine or the MTHFR 677CϾT polymorphism as etiologic cardiovascular risk factors in healthy women. The magnitude of the association between homocysteine and incident CVD in this study was consistent with a small case-control analysis in these women (25 ) and a recent metaanalysis of observational studies that included predominantly men (2 ), although the findings differ from those of a 24-year prospective study in healthy women that found significant associations with myocardial infarction (26 ). Although case-control studies have tended to report strong associations between homocysteine and CVD, many prospective studies have shown weaker or no associations (1,2 ).…”
Section: Discussionsupporting
confidence: 87%
“…Taken together, these findings do not support a strong role for either homocysteine or the MTHFR 677CϾT polymorphism as etiologic cardiovascular risk factors in healthy women. The magnitude of the association between homocysteine and incident CVD in this study was consistent with a small case-control analysis in these women (25 ) and a recent metaanalysis of observational studies that included predominantly men (2 ), although the findings differ from those of a 24-year prospective study in healthy women that found significant associations with myocardial infarction (26 ). Although case-control studies have tended to report strong associations between homocysteine and CVD, many prospective studies have shown weaker or no associations (1,2 ).…”
Section: Discussionsupporting
confidence: 87%
“…The contribution of this haem-containing enzyme to H 2 S generation likely decreases under conditions of hyperhomocysteinaemia; gasotransmitter synthesis is relatively insensitive to Hcy, indicating that cystathionine c-lyase is largely responsible for enhancing H 2 S generation under conditions of hyperhomocysteinaemia. These findings, it has been suggested, point to an important new role for cystathionine c-lyase in the thiol metabolome and Hcy management (Singh et al 2009) and, as the present data indicate, in contributing to a significant clinical phenotype associated with substantial rates of morbidity and mortality (Kearney et al 2005;Reynolds et al 2007;Inoue et al 2007;Elliott 2005;Schultz et al 2007;Paoletti et al 2006;Parnetti et al 2004;Zylberstein et al 2004;Boushey et al 1995;Zhou et al 2001;Sutton-Tyrell et al 1997;Nygard et al 1997). Since H 2 S is highly reactive and has long been considered as toxic, its impact on various tissues is well characterised, but with recent advances in our knowledge, implicating H 2 S in Alzheimer's disease, epilepsy and stroke (Gadalla and Snyder 2010;Gupta et al 2010) as well as hypertension, future development of drugs specifically modulating H 2 S levels is likely to prove beneficial (Gupta et al 2010).…”
Section: Discussionsupporting
confidence: 62%
“…It is well recognised that Hcy acts as an independent risk factor for CVD, including hypertension (Parnetti et al 2004;Zylberstein et al 2004;Boushey et al 1995;Zhou et al 2001;Sutton-Tyrell et al 1997;Nygard et al 1997). In this context, much work has been published in relation to the role of folic acid nutrition and genetics in lowering Hcy, including the beneficial effects of vitamins B 12 and B 6 (Lucock 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These differences both for AMI and for death due to AMI were apparent after 15 years of follow-up. 18 In our study women were not affected at all from high Hcy concentrations -in any of the parameters that were studied (survival, chest pain, CVA). In a study that examined Hcy concentration in patients with coronary artery disease it was found that patients with coronary artery ectasia and coronary artery disease had higher Hcy concentrations than controls.…”
Section: Discussionmentioning
confidence: 51%